Performance optimization method of GFDM system based on WFRFT spectral precoding - Zhenduo WANG; Zhaohui WANG; Ruoyu ZHANG (Tongxin xuebao)
Generalized frequency division multiplexing (GFDM) system always faces challenges related to out-of-band (OOB) power leakage and a high peak-to-average power ratio (PAPR).Through an in-depth analysis of power spectrum characteristics of spectrally precoded GFDM systems, a universal spectral precoding (SP) framework based on the weighted fractional Fourier transform (WFRFT) was established.A two-dimensional parameter-adjustable WFRFT-SP-GFDM system was introduced.By flexibly configuring the parameters, the WFRFT spectral precoder could be made to approximate the weighted fractional Fourier transform matrix, achieve precise control over OOB power and PAPR.Simulation results indicate that, when compared to conventional GFDM and WFRFT-GFDM waveforms, the WFRFT-SP-GFDM waveform effectively suppresses OOB power leakage, while maintaining favorable PAPR and bit error rate (BER) performance.